New chemodosimetric reagents as ratiometric probes for cysteine and homocysteine and possible detection in living cells and in blood plasma - Das, Priyadip; Mandal, Amal Kumar; Chandar, Nellore Bhanu; Baidya, Mithu; Bhatt, Harshad B.; Ganguly, Bishwajit; Ghosh, Sudip K.; Das, Amitava (Chemistry a European Journal, 2012)
In this work, we have rationally designed and synthesized two new reagents (L1 and L2), each bearing a pendant aldehyde functionality. This aldehyde group can take part in cyclization reactions with β- or γ-amino thiols to yield the corresponding thiazolidine and thiazinane derivatives, respectively. The intramolecular charge-transfer (ICT) bands of these thiazolidine and thiazinane derivatives are distinctly different from those of the molecular probes (L1 and L2). Such changes could serve as a potential platform for using L1 and L2 as new colorimetric/fluorogenic as well as ratiometric sensors for cysteine (Cys) and homocysteine (Hcy) under physiological conditions. Both reagents proved to be specific towards Cys and Hcy even in the presence of various amino acids, glucose, and DNA. Importantly, these two chemodosimetric reagents could be used for the quantitative detection of Cys present in blood plasma by using a pre-column HPLC technique. Such examples are not common in contemporary literature. MTT assay studies have revealed that these probes have low cytotoxicity. Confocal laser scanning micrographs of cells demonstrated that these probes could penetrate cell membranes and could be used to detect intracellular Cys/Hcy present within living cells. Thus, the results presented in this article not only demonstrate the efficiency and specificity of two ratiometric chemodosimeter molecules for the quantitative detection of Cys and Hcy, but also provide a strategy for developing reagents for analysis of these vital amino acids in biological samples.
Keywords: charge transfer; chemodosimetric detection; cysteine/ homocysteine sensors; fluorescent probes; imaging agents; ratiometric probes

Role of metal ion in specific recognition of pyrophosphate ion under physiological conditions and hydrolysis of the phosphoester linkage by alkaline phosphatase - Das, Priyadip; Chandar, Nellore Bhanu; Chourey, Shishir; Agarwalla, Hridesh; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2013)
Complexes synthesized from Zn(II), Cu(II), and Cd(II), using a dipicolyl amine derivative (L), showed unique specificity toward pyrophosphate ion (PPi or P4O74-) among all other common anionic analytes, including different biologically significant phosphate ion (PO43-, H2PO42-) or phosphate-ion-based nucleotides, such as AMP, ADP, ATP, and CTP. However, the relative affinities of PPi toward these three metal complexes were found to vary and follow the order K-a(L.Zn-PPi) > are given in units of (L.Cu-PPi)(a) >= K-a(L.Cd-PPi). Luminescence responses of the receptor L were substantial on binding to Zn2+ and Cd2+, while relatively a much smaller luminescence response was observed in the presence of Cu2+. Luminescence responses of L.M-PPi (M is Zn2+, Cd2+, and Cu2+) were further modified on binding to the PPi ion. This could be utilized for quantitative detection of PPi in physiological condition as well as for developing a real time ``turn-on'' (for L.Zn and L.Cu) and ``turn-off'' (for L.Cd) fluorescence assay for evaluating the enzymatic activity of alkaline phosphatase (ALP). Experimental results revealed how the subtle differences in the binding affinities between PPi and M in L.M (M is Zn2+, Cd2+, and Cu2+), could influence the cleavage of the phosphoester linkage in PPi by ALP. The DFT calculations further revealed that the hydrolytic cleavage of the metal ion coordinated phosphoester bond is kinetically faster than that for free PPi and thus, rationalized the observed difference in the cleavage of the phosphoester bond by an important mammalian enzyme such as ALP in the presence of different metal complexes.